The Integration of Islamic Educational Philosophy and Neuroscience in Understanding the Nature of the Human Being as an Educational Subject - Muhammad Fadhli Azmi; Muhammad Rafi; Azizah Hanum OK (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
Understanding human nature is fundamental to developing effective education. However, Islamic educational philosophy and neuroscience are often treated as separate disciplines, resulting in a fragmented view of humans as educational subjects. This study aims to examine the integration of Islamic educational philosophy and neuroscience in understanding human nature within the educational context. A qualitative library research design with an integrative-philosophical approach was employed. Data were collected from books, scholarly journal articles, and other relevant literature, then analyzed using content analysis and conceptual synthesis. The findings indicate that the Islamic concept of fitrah corresponds with the neuroscience concept of neuroplasticity, emphasizing the dynamic potential of human development. Furthermore, integrating the concepts of 'aql, qalb, nafs, and ruh with neuroscientific perspectives provides a more comprehensive understanding of learners as biological, cognitive, moral, and spiritual beings. This integration also supports the development of holistic educational practices that balance intellectual, emotional, moral, and spiritual growth. The study concludes that integrating Islamic educational philosophy and neuroscience offers a comprehensive framework for strengthening contemporary Islamic education.